Strategy for Public Information and Communication Management in Improving the Quality of Public Services(A Study at the Department of Communication and Informatics of Sidoarjo Regency) - Usrotin Choiriyah, Ilmi; UB, A. Riyadh; Alfin Azrial Akbar, Mochammad (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
This research aims to explore the strategies employed by the Communication and Information Agency of Sidoarjo Regency in enhancing the quality of public services. The study utilizes a qualitative research design with data collection techniques including observation, interviews, and documentation. The findings indicate that, firstly, the objectives set by the DISKOMINFO to improve service quality have been achieved and are functioning well. Despite well-defined goals, attention is needed for clearer Standard Operating Procedures (SOP) and a more efficient bureaucratic structure. Secondly, strategic environmental factors involve human resources and infrastructure. Challenges in human resources relate to IT, with only one employee educated in IT. However, existing infrastructure resources, including laptops, printers, and handycams, support efficient public complaints and reporting. Thirdly, actions taken by DISKOMINFO include providing public information transparency through a website and complaint center, utilizing the Public Information Request Form (PPID). Nevertheless, the focus on public information transparency aligns with democratic principles and individual rights.